2002
DOI: 10.1097/01.mp.0000026617.52466.9f
|View full text |Cite
|
Sign up to set email alerts
|

MUC2 Is a Molecular Marker for Pseudomyxoma Peritonei

Abstract: Pseudomyxoma peritonei, a syndrome first described by Rokitansky in 1842, is an enigmatic, often fatal intra-abdominal disease characterized by dissecting gelatinous ascites and multifocal peritoneal epithelial implants secreting copious globules of extracellular mucin. Although much past interest in the syndrome has focused on the question of whether the disease arises from primary appendiceal or ovarian mucinous tumors of varying malignant potential, the accumulation of extracellular mucin with its resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 38 publications
4
57
1
2
Order By: Relevance
“…Interestingly, cases of classic pseudomyxoma peritonei show the intestinal⁄appendiceal pattern (MUC-2+ and MUC-5AC+), as do appendiceal mucinous neoplasms, whereas cases of peritoneal implants or pseudomyxoma ovarii associated with primary ovarian mucinous neoplasms show the ovarian pattern (MUC-2-and MUC-5AC+), just as ovarian mucinous neoplasms do [36] . These findings support the notion that pseudomyxoma peritonei is a disease resulting from the accumulation of extracellular secretory-type mucin, particularly related to MUC-2 overexpression by neoplastic cells, thereby rendering MUC-2 expression a potential molecular target to inhibit the progression of the disease [35,37] .…”
Section: Dissemination From the Primary Tumorsupporting
confidence: 75%
See 1 more Smart Citation
“…Interestingly, cases of classic pseudomyxoma peritonei show the intestinal⁄appendiceal pattern (MUC-2+ and MUC-5AC+), as do appendiceal mucinous neoplasms, whereas cases of peritoneal implants or pseudomyxoma ovarii associated with primary ovarian mucinous neoplasms show the ovarian pattern (MUC-2-and MUC-5AC+), just as ovarian mucinous neoplasms do [36] . These findings support the notion that pseudomyxoma peritonei is a disease resulting from the accumulation of extracellular secretory-type mucin, particularly related to MUC-2 overexpression by neoplastic cells, thereby rendering MUC-2 expression a potential molecular target to inhibit the progression of the disease [35,37] .…”
Section: Dissemination From the Primary Tumorsupporting
confidence: 75%
“…MUC-2 is specifically expressed in goblet cells of the small bowel and colon, while MUC-5AC is generally expressed in the stomach and respiratory tracts. The vast majority of mucinous epithelial neoplasms of the appendix coexpress both MUC-2 and MUC-5AC, while mucinous neoplasms of the ovary express only MUC-5AC but not MUC-2 [35] . Interestingly, cases of classic pseudomyxoma peritonei show the intestinal⁄appendiceal pattern (MUC-2+ and MUC-5AC+), as do appendiceal mucinous neoplasms, whereas cases of peritoneal implants or pseudomyxoma ovarii associated with primary ovarian mucinous neoplasms show the ovarian pattern (MUC-2-and MUC-5AC+), just as ovarian mucinous neoplasms do [36] .…”
Section: Dissemination From the Primary Tumormentioning
confidence: 99%
“…The reporting of CK20 positivity is variable in normal colonic epithelium as it is necessary (as in the current study) to have well-orientated mucosal sections to demonstrate staining in cells in the outer differentiated zone of the intestinal crypt (Hernandez et al, 2005). As in other studies (O'Connell et al, 2002;Mohamed et al, 2004), we demonstrated increased expression of MUC-2 in PMP tissue compared with normal mucosa and adenocarcinoma. Interleukin-9, which induces MUC-2 and MUC-5AC gene expression in the lung, and its receptor, IL-9Ra, were expressed at variable levels in all cases of PMP with increased IL-9 expression in the epithelial PMP cells compared with adenocarcinoma.…”
Section: Discussionsupporting
confidence: 62%
“…Mucin gene overexpression studies, cytokeratin profiles and molecular genetic studies support the conclusion that the appendiceal tumor is the source of pseudomyxoma peritonei and the synchronous ovarian tumors. 85 Rarely, origin of pseudomyxoma peritonei is attributable to an ovarian borderline mucinous tumor associated with a mature teratoma. 25,86,87 Tumors with Noninvasive Carcinoma…”
Section: Pseudomyxoma Peritoneimentioning
confidence: 99%